The VMC survey - XV. The Small Magellanic Cloud-Bridge connection history as traced by their star cluster populations - Piatti, Andres Eduardo (2015)
We present results based on YJKs photometry of star clusters located in the outermost, eastern region of the Small Magellanic Cloud (SMC). We analysed a total of 51 catalogued clusters whose colour-magnitude diagrams (CMDs), having been cleaned from field-star contamination, were used to assess the clusters' reality and estimate ages of the genuine systems. Based on CMD analysis, 15 catalogued clusters were found to be possible non-genuine aggregates. We investigated the properties of 80 per cent of the catalogued clusters in this part of the SMC by enlarging our sample with previously obtained cluster ages, adopting a homogeneous scale for all. Their spatial distribution suggests that the oldest clusters, log(t yr-1) ≥ 9.6, are in general located at greater distances to the galaxy's centre than their younger counterparts - 9.0 = log(t yr-1) ≤ 9.4 - while two excesses of clusters are seen at log(t yr-1) ~ 9.2 and log(t yr-1) ~ 9.7. We found a trail of younger clusters which follow the wing/bridge components. This long spatial sequence does not only harbour very young clusters, log(t yr-1) ~ 7.3, but it also hosts some of intermediate ages, log(t yr-1) ~ 9.1. The derived cluster and field-star formation frequencies as a function of age are different. The most surprising feature is an observed excess of clusters with ages of log(t yr-1) < 9.0, which could have been induced by interactions with the LMC.